The tadpole of Dendropsophus branneri (Cochran, 1948) (Amphibia, Anura, Hylidae) - de Abreu, Rafael Oliveira; Juncá, Flora Acuña; Souza, Isana Carla Amorim; Napoli, Marcelo Felgueiras (Zootaxa, 2015)
Dendropsophus branneri is a small treefrog largely distributed throughout the Tropical Atlantic and Caatinga morphoclimatic domains (see Ab’Sáber 1977 for morphoclimatic domains), from northeastern to southeastern Brazil [Lutz 1973, Frost 2014; see Zina et al. 2014 for taxonomic comments on D. minusculus (Rivero, 1971) and D. branneri]. This species is currently placed in the D. microcephalus species group according to Bastos & Pombal (1996) and Faivovich et al. (2005). The D. microcephalus group comprises 36 species (Frost 2014), 14 of which have known tadpoles. Here, we describe the external morphology and color patterns of the previously unknown tadpole of D. branneri.